2020
DOI: 10.5194/amt-13-5779-2020
|View full text |Cite
|
Sign up to set email alerts
|

Commercial microwave links as a tool for operational rainfall monitoring in Northern Italy

Abstract: Abstract. There is a growing interest in emerging opportunistic sensors for precipitation, motivated by the need to improve its quantitative estimates at the ground. The scope of this work is to present a preliminary assessment of the accuracy of commercial microwave link (CML) retrieved rainfall rates in Northern Italy. The CML product, obtained by the open-source RAINLINK software package, is evaluated on different scales (single link, 5 km×5 km grid, river basin) against the precipitation products operation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
0
19
0
1
Order By: Relevance
“…One barrier to a more generalized used of CML data is the potentially wider availability of such privately owned data sets: there remains a large variability in the conditions of access to such data. In the present case data was accessible to the authors but protected by a Non-Disclosure agreement, as seen also in Graf et al (2020), while in others the data is freely available (de Vos et al, 2018a) or available upon purchase (Roversi et al, 2020). The uniqueness of CML data is their worldwide distribution, and the presence of infrastructure collecting data in remote and unmonitored regions where other techniques are unavailable.…”
Section: Discussionmentioning
confidence: 91%
“…One barrier to a more generalized used of CML data is the potentially wider availability of such privately owned data sets: there remains a large variability in the conditions of access to such data. In the present case data was accessible to the authors but protected by a Non-Disclosure agreement, as seen also in Graf et al (2020), while in others the data is freely available (de Vos et al, 2018a) or available upon purchase (Roversi et al, 2020). The uniqueness of CML data is their worldwide distribution, and the presence of infrastructure collecting data in remote and unmonitored regions where other techniques are unavailable.…”
Section: Discussionmentioning
confidence: 91%
“…As it was noted by [11], maintenance of dedicated equipment for retrieval of the needed reference rainfall observations is impractical for such networks. Thus, application-focused studies with city or regional-scale CML networks have often not applied any WAA correction at all [12], [13] or have used only a simple constant offset model [3], [14], [15], [16]. Although the latter approach may be a reasonable choice when only 15-min TRSL maxima and minima are available [2], it can introduce a considerable bias in the resulting CML QPEs [3], [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we analyze for the first time six empirical WAA models, including a newly proposed one, based on considerably different assumptions and test in detail their performance. In contrast to previous studies, often limited by a low number of CMLs investigated [4], [7], [10], short time series of a few months [7], [14], [15] or 15-min CML data sampling intervals [14], [19], we use a rich dataset of more than two years of data retrieved from 16 CMLs with a sub-minute sampling rate. Motivated by the vision of reducing the costs of future studies with high numbers of CMLs, we also address the previously recognized need [11], [18] to minimize the amount of auxiliary data necessary for WAA estimation without compromising the quality of retrieved QPEs, and thus, we introduce three conceptual innovations not previously presented in relevant literature: Firstly, we show how the investigated empirical WAA models can be calibrated while notably minimizing the requirements on the reference rainfall data necessary, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Authors found out that the bias propagated thoughout simulations is inversely proportional to CML length. In Italy, Roversi et al (2020) conducted a meteorological analysis in the Po valley in Emilia Romagna (northern Italy) to assess the accuracy of CML retrieved rainfall rates using data purchased from Vodafone.…”
Section: Introductionmentioning
confidence: 99%